Fe-doped effects on phase transition and electronic structure of CeO2 under compressed conditions from ab initio calculations - Sathupun, Karnchana; Kotmool, Komsilp; Tsuppayakorn-aek, Prutthipong; Pluengphon, Prayoonsak; Majumdar, Arnab; Bovornratanaraks, Thiti (My University, 2021)
Ab initio study of high-pressure phase transition and electronic structure of Fe-doped CeO2 with Fe concentrations of 3.125, 6.25, and 12.5 at% has been reported. At a constant-pressure consideration, the lattice constants and the volume of the supercell were decreased with an increasing concentration of Fe. The average bond length of Fe–O is lower than that of Ce–O. As a result, Fe doping induces the reduced volume of the cell, which is in good agreement with previous experiments. At high pressure (~ 30 GPa), it was found that the transition pressure from the fluorite to the cotunnite orthorhombic phase decreases at a higher concentration of Fe, indicating that the formation energy of the compound is induced by Fe-doping. Furthermore, compression leads to interesting electronic properties too. Under higher pressures, the bandgap increases in the cubic structure under compression and then suddenly plummets after the transition to the orthorhombic phase. The 3d states of Fe mainly induced the impurity states in the bandgap. In both the undoped and Fe-doped systems, the bandgap increased in the cubic phase at high pressure, while the gap and p-d hybridization decrease in the orthorhombic phase.
Keywords: CeO2; Electronic structure; Fe-doped; High pressure; Phase transition